Relevance of body size and shell colouration for thermal absorption and heat loss in white garden snails, Theba pisana (Helicidae), from Northern France. (October 2017) - Knigge, Thomas; Di Lellis, Maddalena A.; Monsinjon, Tiphaine; Köhler, Heinz-R.
Abstract: The internal temperature of land snails depends on environmental factors, such as exposure to electromagnetic radiation and airflow as well as biotic factors including shell size, shell colouration and thickness or the resting position of the snail. In controlled field experiments, we quantified heating by thermal absorption of light and airflow-induced heat loss in the white garden snail, Theba pisana, from Normandy, France. Heating experiments revealed a significant positive relation of the internal body temperature with illumination period, shell temperature and air temperature at different times of day. The size of the snails was negatively related with both of the given illumination times: smaller animals heated up stronger than larger ones. The temperature at the surface of the shell significantly depended on the illumination period and the time of day. An AIC-based quality assessment of multiple linear modelling showed that, for explaining both shell surface and internal temperature of the soft body, several factors, i.e., exposure time, daytime, shell size and colouration contributed to the best models, respectively. Similarly, heat loss of the soft body after and during exposure of the snails to sunlight by a constant airflow depended on the initial body temperature, shell size, colouration and ambient air temperature. Our study revealed also the importance of both shell size and colouration for the loss of body temperature under natural conditions: small and banded animals that had heated up to temperatures above 30 °C cooled down faster than large and un-banded ones. Highlights: Thermal exchange between land snails and environment is mainly influenced by size. Equilibrium temperature is determined by the ambient temperature. Shell colouration does not alter the equilibrium temperature of ectothermic snails. Shell colouration affects the rate with which animals react to thermal changes.